Automated quantification system for vision through polymer‐dispersed liquid crystal double‐glazed windows: Circuit implementation. Issue 1 (27th November 2022) - Lami, Mohammed; Al‐naemi, Faris; Issa, Walid
Abstract: Polymer‐dispersed liquid crystal automated quantification system for vision through polymer‐dispersed liquid crystal double‐glazed windows: Circuit implementation (PDLC)‐windows played an essential role in providing a visual comfort for occupants in commercial buildings recently. PDLC windows adjust the visible transparency of the glazing to control the daylight accessed to internal environments. A former study proposed an algorithm to quantify the vision through the PDLC glazing in terms of image contrast. The quantification algorithm determines the minimum level of transparency that maintains a comfortable vision through the window. This study introduced the implementation of a real‐time automated system that achieves the vision quantification process. Firstly, system on‐chip was utilised to realise the quantification algorithm, including contrast estimation. Secondly, the contrast determination action was re‐implemented using MATLAB, Cortex‐A9 microcontroller, and Cyclone V field programmable gate array field programmable gate array‐chip. The implemented systems were evaluated based on the latency, throughput, power consumption, and cost. Abstract : Embedded circuit realisation. System on‐chip. Quantifying of vision through PDLC film.